Reconfigurable Circular-Ring Feed Patch Antenna with Tri-Polarization Diversity - Gu, Hui; Ge, Lei; Zhang, Jihong (Frontiers in Physics, 2021)
In this paper, a reconfigurable circular-ring feed patch antenna for polarization diversity applications is proposed. The reconfigurability is realized by using only two p-i-n diodes which are inserted into the circular feed ring of the aperture-coupled patch antenna. With the help of the p-i-n diodes, the polarization of the antenna is able to be altered among 45o linearly polarized (LP), left-hand circularly polarized (LHCP), and right-hand circularly polarized (RHCP) states. A fully-functional prototype is fabricated and measured. The measurement agrees well with the simulation and three polarization states are obtained. Owing to the merits of tri-polarization diversity, low profile and simple structure, the proposed design is a great candidate for future wireless systems.